Bridging the Surface Charge and Catalytic Activity of a Defective Carbon Electrocatalyst. (3rd January 2019) - Tao, Li; Qiao, Man; Jin, Rong; Li, Yan; Xiao, Zhaohui; Wang, Yuqing; Zhang, Nana; Xie, Chao; He, Qinggang; Jiang, Dechen; Yu, Gang; Li, Yafei; et al.
Abstract: Electrocatalysis is dominated by reaction at the solid–liquid–gas interface; surface properties of electrocatalysts determine the electrochemical behavior. The surface charge of active sites on catalysts modulate adsorption and desorption of intermediates. However, there is no direct evidence to bridge surface charge and catalytic activity of active sites. Defects (active sites) were created on a HOPG (highly oriented pyrolytic graphite) surface that broke the intrinsic sp 2 ‐hybridization of graphite by plasma, inducing localization of surface charge onto defective active sites, as shown by scanning ion conductance microscopy (SICM) and Kelvin probe force microscopy (KPFM). An electrochemical test revealed enhanced intrinsic activity by the localized surface charge. DFT calculations confirmed the relationship between surface charge and catalytic activity. This work correlates surface charge and catalytic activity, providing insights into electrocatalytic behavior and guiding the design of advanced electrocatalysts.